18th International Conference and Exhibition on Electricity Distribution (CIRED 2005) 2005
DOI: 10.1049/cp:20050947
|View full text |Cite
|
Sign up to set email alerts
|

Internal arc fault testing of gas insulated metal enclosed MV switchgear

Abstract: An investigation on internal arc fault tests in gas-insulated metal enclosed MV switchgears is described and discussed. The influence of different gases (SF 6 and air) and electrode materials (Cu, Al, and Fe) has been put into evidence. This is highly relevant based on the fact that IEC Standards and utilities technical specifications allows that internal arc fault tests are performed with air replacing SF 6 with some precautions. The experimental tests were carried out at NEFI High Power Laboratory in Skien, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…At a first approximation it may be concluded that the extra energy input caused by Cu vapors reacting exothermally with the surrounding air is most probably negligible. This is however in contrast to the strong exothermal reaction between vaporized aluminum and dissociated SF 6 reported by Bjørtuft et al [5]. For the moving arc with no gross melting, relevant information is relatively scarce in the literature.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…At a first approximation it may be concluded that the extra energy input caused by Cu vapors reacting exothermally with the surrounding air is most probably negligible. This is however in contrast to the strong exothermal reaction between vaporized aluminum and dissociated SF 6 reported by Bjørtuft et al [5]. For the moving arc with no gross melting, relevant information is relatively scarce in the literature.…”
Section: Discussionmentioning
confidence: 79%
“…To get a better understanding of the influence of chemical reactions, it is assumed that the reactions contribute significantly only if the released energy is more than 10 % of the total arc energy. Table V shows the assumed amount of copper, ∆m Wchem , which will have to react chemically, according to equation (5), for a 10 % extra contribution to the arc energy input. It may be assumed that an exothermic reaction will to a large extent depend on Cu being present in vapor form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio kp of energy contributing to the internal pressure rise and the arc energy depends on a number of parameters, such as the physical properties of the arc and gas, the material and shape of electrodes, the size and shape of closed container, and so on . Here, we report the results obtained in these experiments regarding kp in air and SF 6 gas.…”
Section: Resultsmentioning
confidence: 96%
“…For air at ambient temperature, the adiabatic coefficient κ is about 1.4 [22]. c v is the specific heat of the gas at constant volume.…”
Section: Determination Of the "K P -Factor"mentioning
confidence: 99%